Obesity and the Incidence of Bladder Injury and Urinary Retention Following Tension-Free Vaginal Tape Procedure: Retrospective Cohort Study - Vladimir Revicky; Sambit Mukhopadhyay; Frances de Boer; Edward P. Morris (Obstetrics and Gynecology International)
Background/Aims. Aim of the study was to establish an effect of obesity on the incidence of bladder injury or urinary retention following tension-free vaginal tape (TVT) procedure. Methods. This was a retrospective cohort study based at the Norfolk and Norwich University Hospital in the UK. Study population included 342 cases of TVT procedures. Incidence of bladder injury was 4.7% (16/342). Rate of urinary retention was 9% (31/342). Body mass index (BMI), age, type of analgesia, concomitant prolapse repair, and previous surgery were factors studied. Univariate analysis was performed to establish a relationship between BMI and complications, followed by a multivariable regression analysis to adjust for age, concomitant surgery, type of analgesia, and previous surgery. Results. Neither univariate analysis nor multivariate regression analysis revealed any statistically significant influence of obesity on the incidence of bladder injury or urinary retention. Unadjusted odds ratios and adjusted odds ratios for bladder injury and urinary retention by BMI groups were OR 1.7296 CI 0.4818–6.2097; OR 1.3745 CI 0.5718–3.3043 and adj. OR 2.885 CI 0.603–13.8; adj. OR 1.299 CI 0.502–3.365. Conclusion. Obesity does not appear to influence the rate of bladder injury or urinary retention following TVT procedure.